Covid-19 and the impact of virtual learning on the mental health of higher education students - Nur Izzati Umairah Mokhtar,; Roziana Bahari, (Penerbit Universiti Kebangsaan Malaysia, 2003)
The impact of the COVID-19 pandemic has serious implications for the education aspect. Therefore, in order to reduce the spread of the epidemic, the Malaysian government has ordered the implementation of the Movement Control Order (MCO). This MCO has limited many activities including the learning process, where it needs to be changed from face-to-face learning to online learning. This situation certainly has a serious impact on students, especially from the mental health aspect because they have to adapt to the new learning process. Therefore, this study was conducted to find out the challenges of online learning and its impact on the mental health o Higher Education Institution (HEI) students during the pandemic. This study has 155 respondents from HEI students to answer the questionnaire through the google form platform and distributed using social media to facilitate the study. The findings of the study found that the main challenge in implementing this online learning because it affects mental health is the problem of heavy workload. The impact on mental health is that the majority experience anxiety at a serious level. This study also suggests not to hide the problem itself and to have a strong resilience strategy so that the problem can be overcome.